Enabling adoption of 2D-NMR for the higher order structure assessment of monoclonal antibody therapeutics. Issue 1 (2nd January 2019) - Brinson, Robert G.; Marino, John P.; Delaglio, Frank; Arbogast, Luke W.; Evans, Ryan M.; Kearsley, Anthony; Gingras, Geneviève; Ghasriani, Houman; Aubin, Yves; Pierens, Gregory K.; Jia, Xinying; Mobli, Mehdi; et al.
ABSTRACT: The increased interest in using monoclonal antibodies (mAbs) as a platform for biopharmaceuticals has led to the need for new analytical techniques that can precisely assess physicochemical properties of these large and very complex drugs for the purpose of correctly identifying quality attributes (QA). One QA, higher order structure (HOS), is unique to biopharmaceuticals and essential for establishing consistency in biopharmaceutical manufacturing, detecting process-related variations from manufacturing changes and establishing comparability between biologic products. To address this measurement challenge, two-dimensional nuclear magnetic resonance spectroscopy (2D-NMR) methods were introduced that allow for the precise atomic-level comparison of the HOS between two proteins, including mAbs. Here, an inter-laboratory comparison involving 26 industrial, government and academic laboratories worldwide was performed as a benchmark using the NISTmAb, from the National Institute of Standards and Technology (NIST), to facilitate the translation of the 2D-NMR method into routine use for biopharmaceutical product development. Two-dimensional 1 H, 15 N and 1 H, 13 C NMR spectra were acquired with harmonized experimental protocols on the unlabeled Fab domain and a uniformly enriched- 15 N, 20%- 13 C-enriched system suitability sample derived from the NISTmAb. Chemometric analyses from over 400 spectral maps acquired on 39 different NMR spectrometers ranging from 500 MHz to 900 MHz demonstrate spectral fingerprints that are fit-for-purpose for the assessment of HOS. The 2D-NMR method is shown to provide the measurement reliability needed to move the technique from an emerging technology to a harmonized, routine measurement that can be generally applied with great confidence to high precision assessments of the HOS of mAb-based biotherapeutics.